SWEET POTATO IPOMOEA BATATAS FLOUR FOR VEGGIE-FRUIT BUMPER PRODUCTION: TECHNOLOGY DISSEMINATION AND ADOPTION - Giango, Wilma C (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
Sweet potato Ipomoea batatas is a very popular root crop in the tropics which can be made into several delicacies or food item in terms of product development. This study was an experimental design conducted in a factorial experiment with four main treatment or plot represented by the flour used in making the crust and a sub plot represented by the three different kinds of veggie-fruit filling materials. The study was conducted to determine the formulation of veggie- fruit bumper locally known as “Empanaditas” using sweet potato (SP) flour with different ratio of all- purpose flour as crust. The crust were filled with varied veggie-fruit fillings such as squash, mango, pineapple, turnip, chayote and carrots. The ratio of the sweet potato flour with all- purpose flour in making the crust were as follows: Treatment 1=100% allpurpose flour (Control); Treatment 2=75% all-purpose flour + 25% (SP) flour; Treatment 3=50% all-purpose flour + 50% (SP) flour; and Treatment 4=25% all-purpose flour + 75 % (SP) flour. These crust were filled with vegetables and fruits as filling such as squash, mango, pineapple (Mixture A); mango, turnip, pineapple (Mixture B); and, chayote, carrot, pineapple (Mixture C). The acceptability of the product was determined through the crust and the veggie-fruit mixture as filling using the quality attributes of color, aroma, texture, and taste. The proximate nutritional analysis of the most preferred recipe was also determined. Based on the findings of the study, 50% sweet potato flour was tested to be a good ingredient in making pastry crust. Veggie-fruit filling from the mixture of squash, mango, and pineapple was found the most acceptable formulation with the use of 50% sweet potato flour as crust.